Oog voor elkaar - Blokland, Talja (Amsterdam University Press, 2021)
People like to live in a safe neighborhood. Areas with a variety of facilities like houses, offices and shops seem to be an important strategy to improve the safety of a neighborhood. More people on the streets means better social control, is the thought behind this strategy. But do people on the streets have consideration for each other? This book is a theory on urban environment, public familiarity and trust on the one hand. On the other it is a very practical plea for a careful planning and nuanced governance of the public space.